2011
DOI: 10.1051/0004-6361/201117504
|View full text |Cite
|
Sign up to set email alerts
|

Strong chaos induced by close encounters with Ceres and Vesta

Abstract: We consider the full Solar System including (1) Ceres and some of the main asteroids, (2) Pallas, (4) Vesta, (7) Iris, and (324) Bamberga. We show that close encounters among these small bodies induce strong chaotic behavior in their orbits and in those of many asteroids that are much more chaotic than previously thought. Even if space missions will allow very precise measurements of the positions of Ceres and Vesta, their motion will be unpredictable over 400 kyr. As a result, it will never be possible to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
199
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(211 citation statements)
references
References 19 publications
12
199
0
Order By: Relevance
“…(10) gives a jump size of 1.3 AU. The probability of such an encounter can be evaluated using the same approach as in Laskar et al (2011). We obtain a number of encounters closer than the diameter of Vesta (without colliding, i.e., farther away than the radius of Vesta) of about 7 × 10 −4 per Gyr and per fragment.…”
Section: Very Close Encountersmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) gives a jump size of 1.3 AU. The probability of such an encounter can be evaluated using the same approach as in Laskar et al (2011). We obtain a number of encounters closer than the diameter of Vesta (without colliding, i.e., farther away than the radius of Vesta) of about 7 × 10 −4 per Gyr and per fragment.…”
Section: Very Close Encountersmentioning
confidence: 99%
“…In the second simulation (S E) the 11 asteroids were considered as the planets and accordingly interact with members of the synthetic Vesta family. Both solutions are integrated over 30 Myr using the symplectic integrator described in Laskar et al (2011) and references therein. The effects of all planets and Pluto are taken into account, as is general relativity.…”
Section: Introductionmentioning
confidence: 99%
“…regions characterized by high collision probabilities with one of the most massive asteroids. Recently, Laskar et al (2011) showed that when the five major bodies were included in simulations with all the planets, surprisingly, not only the orbits of the major asteroids were more chaotic, but even the precision with which the orbital elements of the Earth are known was limited to 50 Myr. Delisle & Laskar (2012) investigated the orbital mobility in the Vesta family region caused by close encounters with eleven major asteroids, and found that most of the mobility is caused by encounters with (4) Vesta and (1) Ceres, and is on the order of magnitude of what is found in previous works (Carruba et al 2003(Carruba et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Oligo-Miocene presents an opportunity to study the dynamics of a unipolar (Antarctic) icehouse climate state without the overprint of Northern Hemisphere ice sheets on benthic foraminiferal δ 18 O records. Published proxy records of atmospheric CO 2 concentration show a decline from the Oligocene to the Miocene (6, 7) that is broadly contemporaneous with a strong minimum in the ∼2.4-My eccentricity cycle ∼24 My ago (8), which would promote continental ice sheet expansion if radiative forcing was the dominant control on ice volume. Previous studies using drill core records from the deep ocean demonstrate a climatic response to astronomical forcing for the Oligocene (9,10) and parts of the Miocene (11)(12)(13).…”
mentioning
confidence: 99%